Postoperative Radiotherapy of Keloid Earlobe at Dr. Kariadi Hospital - Kurniati, Endah (International Journal of Allied Medical Sciences and Clinical Research, 2021)
This study aims to determine the radiation therapy procedure in postoperative cases of keloid earlobe at Dr Kariadi Semarang. Postoperative radiotherapy for keloid earlobe is very effective to prevent recurrence and treat keloid because it can suppress fibroblast activity but is still rarely used. The results showed that there was no specific preparation in postoperative radiation therapy for earlobe keloids. Earlobe keloid radiotherapy was performed within 24 hours postoperatively, using silicone as a bolus and using 6 MeV electrons. The total dose given was 16 Gy with 4x4 Gy fractionation